Middle Ages-Reformation-Volkskunde Festschrift for John G. Kunstmann - Coenen, Frederic E. (UNC Studies in the Germanic Languages and Literatures, 1959)
Twenty essays on medieval history, literature and language published in honor of John G. Kunstmann and his work on German literature in the Middle Ages. The contributors are Berthold Ullman, Urban Tigner Holmes, Edwin Zeydel, George Fenwick Jones, Wayland Hand, Robert Linker, John Keller, Carl Bayerschmidt, Helmut Motekat, Stuart Gallacher, John Fisher, Astrik Gabriel, James Engel, Eli Sobel, Lewis Spitz, Theodore Silverstein, Murray Cowie, Marian Cowie, Josef Ryan, Oscar Jones, and Fritjof Raven.